605 Systemically administered HER2-targeted ISACs provoke a rapid, local response that engages the innate and adaptive arms of the immune system to eradicate tumors in preclinical models. (9th November 2020) - LeBlanc, Heidi; Pearson, Cecelia; Kenkel, Justin; Blum, LIsa; Ho, Po; Luo, Angela; Laura, Richard; Zhou, Matthew; Gregorio, Joshua; Luo, Andrew; Ackerman, Shelley; Safina, Brian; et al.
Abstract : Background: Immune-stimulating antibody conjugates (ISACs) covalently attach immune stimulants to tumor-targeting antibodies such as trastuzumab. We have shown that HER2-targeted TLR7/8 ISACs elicit robust myeloid activation and tumor eradication in a TLR- and Fc-dependent manner in trastuzumab-resistant and HER2-low models. Upon treatment with ISACs, T cell-mediated immunological memory extends to tumor antigens beyond HER2. 1 Here we describe the ISAC mechanism of action in vivo that leads to eradication of tumors in mice. Methods: Established syngeneic rHER2- or xenograft HER2-expressing tumors treated with anti-HER2 ISACs or appropriate controls were assessed for gene expression by NanoString Pan-Cancer Immune Profiling panel comprising 750 genes related to tumor immune biology. Tumor cytokines were measured using MesoScale Discovery (MSD) technology, and immune cell infiltrates were assessed by immunohistochemistry (IHC). Anti-tumor efficacy was assessed after depletion of CD8+ T cells and phagocytes. Results: Within 24 hours of administration, HER2-directed ISACs induced robust, target-dependent activation of the immune system. In a syngeneic tumor model, 34% of the measurable genes were significantly upregulated after treatment with the rHER2-targeted ISAC vs 0.1% with the non-binding ISAC control. Similarly, 13% vs 0% of genes were upregulated in a xenograft model after HER2-targeted vs control ISAC treatment. In both models anti-HER2 ISAC treatment led to activation of pathways indicative of TLR7/8 agonism (e.g. IRF-7; type 1 interferons), and FcgR engagement (e.g. NF-kappaB associated genes). Cytokines and chemokines, including myeloid chemokines CCL2/3/4 and T cell chemokines CXCL9/10/11 were specifically upregulated in the tumors at the gene and protein level, indicating robust activation of myeloid cells following anti-HER2 ISAC treatment. Furthermore, in syngeneic tumors T cell activation markers (e.g. Granzyme B; IFN-gamma) were induced within 24 hours post treatment with an anti-rHER2 ISAC, and IHC at day 6 showed a 5-fold increase in CD11c+ cells. Control-treated tumors had sparse CD8+ T cells, whereas rHER2-targeted ISAC treatment led to ~3.5-fold increase in T cell frequency that shifted the tumor microenvironment from immunologically cold to hot. The recruitment of both phagocytes and CD8+ T cells was consequential, as depletion of either abrogated anti-tumor efficacy of the rHER2-targeted ISAC. Systemically delivered ISACs were well-tolerated. Conclusions: In contrast to other immune therapies, such as anti-PDL1/PD1 and anti-CD40, systemically administered ISACs locally engage both the innate and adaptive arms of the immune system to eradicate tumors. The molecular and cellular phenotype associated with ISAC-mediated activation is being evaluated in the on-going BDC-1001 Phase I/II clinical trial. 2 Reference: Ackerman Set al, Poster# P756, SITC 20192. Phase 1/2 Study of BDC-1001 as a Single Agent and in Combination With Pembrolizumab in Patients With Advanced HER2-Expressing Solid Tumors; ClinicalTrials.gov (NCT04278144 )